Life flight [large type] - Eason, Lynette (Eason, Lynette. Extreme measures, 2022)
""A heart-stopping, breath-stealing masterpiece of romantic suspense!"-- Colleen Coble, USA Today bestselling author ***EMS helicopter pilot Penny Carlton is used to high stress situations, but being forced to land on a mountain in a raging storm with a critical patient--and a serial killer on the loose--tests her skills and her nerve to the limit. She survives with FBI Special Agent Holt Satterfield's help. But she's not out of the woods yet.In the ensuing days, Penny finds herself under attack. And when news reaches Holt that he may not have gotten his man after all, it will take all he and Penny have to catch a killer--before he catches one of them.Bestselling and award-winning author Lynette Eason is back with another high-octane tale of close calls, narrow escapes, and the fight to bring a nefarious criminal to justice"--